Applying geomorphological principles and engineering science to develop a phased sediment management plan for Mount St Helens, Washington - Sclafani, Paul; Nygaard, Chris; Thorne, Colin R. (Wiley, 2018)
Thirty-seven years post-eruption, erosion of the debris avalanche at Mount St. Helens continues to supply sediment to the Toutle-Cowlitz River system in quantities that have the potential to lower the Level of Protection (LoP) against flooding unacceptably, making this one of the most protracted gravel-bed river disasters to date. The Portland District, US Army Corps of Engineers (USACE) recently revised its long-term plan for sediment management (originally published in 1985), in order to maintain the LoP above the Congressionally-authorised level, while reducing impacts on fish currently listed under the Endangered Species Act, and minimising the overall cost of managing sediment derived from erosion at Mount St Helens. In revising the plan, the USACE drew on evidence gained from sediment monitoring, modelling and uncertainty analysis, coupled with assessment of future LoP trends under a baseline scenario (continuation of the 1985 sediment management strategy) and feasible alternatives. They applied geomorphological principles and used engineering science to develop a Phased Sediment Management Plan that allows for uncertainty concerning future sediment yields by implementing sediment management actions only as, and when, necessary. The phased plan makes best use of the potential to enhance the sediment trap efficiency and storage capacity of the existing Sediment Retention Structure (SRS) by incrementally raising its spillway and using novel hydraulic structures to build islands in the NFTR and steepen the gradient of the sediment plain upstream of the structure. Dredging is held in reserve, to be performed only when necessary to react to unexpectedly high sedimentation events or when the utility of other measures has been expended. The engineering-geomorphic principles and many of the measures in the Phased Sediment Management Plan are transferrable to other gravel-bed river disasters. The overriding message is that monitoring and adaptive management are crucial components of long-term sediment-disaster management, especially in volcanic landscapes where future sediment yields are characterised by uncertainty and natural variability.